Actual status and proposals for renovation of salary policies for scientists in links with orientations of reforms of salary policies in the new stage - Hai, Ha Cong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
Renovation of salary policies for scientists in public science-technology organizations stops being a new problem. They were put high in considerations from many years. Recently, the Government has made efforts to adjust salary policies for scientists. Up to now, however, the salary policies for scientists in public science-technology organizations still remain with many limitations and shortages. This paper provides analysis on the actual status of salary policies for scientists in public science-technology organizations and, on this basis, makes some proposals for renovation of salary policies for scientists in links with orientations of reforms of salary policies by the Party and the State in the new stage. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;"> Code: 20022401